Analysis, synthesis, and design of chemical processes - Turton, Richard, 1955- (Prentice-Hall international series in the physical and chemical engineering sciences., 2009)
This title presents design as a creative process that integrates both the big picture and the small details - and knows which to stress when, and why. Realistic from start to finish, it moves readers beyond classroom exercises into open-ended, real-world process problem solving.